The Effect of Information Gap Strategy on Learning Dribbling and Scoring Skills in Football for Students - Munshid, Sakhi Kareem; Swadi, Ali Jasim (Journal of Neonatal Surgery, 2025)
Importance of the Study: The significance of this research lies in its rigorous scientific endeavor to utilize the information gap strategy, a form of active learning, which the researchers believe has a positive impact on the acquisition of fundamental soccer skills, including dribbling. Research Objectives: This study aims to investigate the effect of the information gap strategy on learning dribbling and shooting skills. Methodology: The study sample consisted of first-year students from the College of Physical Education and Sports Sciences at Al Ain University during the first semester of the academic year 2024-2025. The researchers employed an experimental design with two equivalent groups: a control group and an experimental group. Key Findings: The primary findings revealed that the experimental group, which implemented the information gap strategy, significantly outperformed the control group, which received traditional instructor-led teaching, in learning dribbling and shooting skills in soccer. Recommendations: The researchers recommend conducting further studies that explore the information gap strategy with different samples and at various educational levels not covered in the current study.